2018
DOI: 10.3390/nu10050548
|View full text |Cite
|
Sign up to set email alerts
|

The Food-Specific Serum IgG Reactivity in Major Depressive Disorder Patients, Irritable Bowel Syndrome Patients and Healthy Controls

Abstract: There is an increasing amount of evidence which links the pathogenesis of irritable bowel syndrome (IBS) with food IgG hyperreactivity. Some authors have suggested that food IgG hyperreactivity could be also involved in the pathophysiology of major depressive disorder (MDD). The aim of this study was to compare levels of serum IgG against 39 selected food antigens between three groups of participants: patients with MDD (MDD group), patients with IBS (IBS group) and healthy controls (HC group). The study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 88 publications
0
23
0
2
Order By: Relevance
“…There is increasing evidence that immunoglobulin Gmediated food hyperreactivity may play a role in IBS symptom generation, but results remain contradictory. Recent studies found elevated food-specific immunoglobulin G levels in IBS subjects in comparison to controls (Zar et al, 2005;Lee and Lee, 2017;Karakula-Juchnowicz et al, 2018). In a randomized controlled trial, IBS subjects excluded from their diet the foods responsible for their increased immunoglobulin G levels.…”
Section: The Link Between Dietary Components and Functional Gastrointmentioning
confidence: 99%
“…There is increasing evidence that immunoglobulin Gmediated food hyperreactivity may play a role in IBS symptom generation, but results remain contradictory. Recent studies found elevated food-specific immunoglobulin G levels in IBS subjects in comparison to controls (Zar et al, 2005;Lee and Lee, 2017;Karakula-Juchnowicz et al, 2018). In a randomized controlled trial, IBS subjects excluded from their diet the foods responsible for their increased immunoglobulin G levels.…”
Section: The Link Between Dietary Components and Functional Gastrointmentioning
confidence: 99%
“…Children with ASD are usually reported to have a “leaky gut” ( 32 ), altered gut permeability play a pathogenic role allowing the input of molecules, the gut microbiota can act through the permeability of gut barrier, undigested proteins are also absorbed by the body through an incomplete intestinal mucosal barrier and pass through the blood–brain barrier to activate the immune system in an abnormal way ( 23 ). As in the previous mentioned, food compounds combine with food IgG antibodies to form immune complexes, and triggers immune-inflammatory cascade, which may contribute to low-level systemic inflammation and low-level neuroinflammation, via pathological processes in CNS ( 7 ), like increased expression of Kynurenine ( 33 ), and the inflammatory molecules interleukin (IL-1β), IL-6, IL-17, and tumor necrosis factor (TNF) in the brain ( 34 ). Many neurochemical pathways also involved in ASD, for instance, gamma aminobutyric acid (GABA), glutamate, serotonin, dopamine, oxytocin, vitamin D, Marotta et al ( 35 ).…”
Section: Discussionmentioning
confidence: 97%
“…Food proteins and protein-derived compounds may modulate the immune response in the body. Leaky gut may lead to food-borne components into blood circulation, and resulting in an abnormal immune response and increased levels of circulating pro-inflammatory cytokines (7). Detection of food intolerance usually by test food-specific IgG antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the concept of food-derived inflammatory response and autoimmunity in MDD seems valuable for further exploration, and possibly patients with chronic, recurrent depression, with gastrointestinal and/or extraintestinal autoimmune diseases, might be a subgroup of patients where food-derived IgG hyperreactivity might contribute to the inflammatory response in MDD. In the subsequent study, it was revealed that out of 39 selected food antigens, patients with MDD had significantly higher serum levels of total IgG antibodies and IgG against celery, garlic, and gluten compared with healthy control (177).…”
Section: The Evidence Of the "Leaky Gut" In Depressionmentioning
confidence: 98%